Effectiveness of Problem-Based Learning (PBL) in Improving Students' Mathematical Ability: Results of a Literature Review - Nabilah, Azzah; Utama , Candra (Khalifah : Jurnal Pendidikan Nusantara, 2024)
The application of problem-based learning approaches to mathematics subjects in elementary schools needs to be improved. It is proven through literature review research that this problem-based learning approach has a significant positive effect on optimizing mathematics learning in achieving maximum learning targets for students in class IV SD. The method used in this research is a systematic literature review to review journals and articles related to PBL and math learning outcomes. Data was collected from the Google Scholar database using a method based on PRISMA, the application of the learning model proved to be effective in problem-based learning in Cycle I resulted in an average percentage of student learning outcomes showing a significant increase from 60% in Cycle I to 89% in Cycle II. This shows a percentage increase of 29%. This research concludes that PBL is an effective method to optimize mathematics learning in surpassing maximum learning targets for students in elementary school. Increasing the application of this problem-based learning approach in the application of mathematics lessons in elementary school is very important and needs to be done on an ongoing basis.